A Philological Report Of The Theologus Autodidactus Of Ibn Al-Nafis By Max Meyerhof And Joseph Schacht - Maulana Maulana; Khotimah Khotimah; Imron Rosidi (Jurnal Ushuluddin, 2017)
Ibn al-Nafis is a monumental figure in Islamic scholarship. He wrote a fictional novel entitled “ Al-Risalah al-Kamiliyah fi’l sira al-Nabawiyah” which is translated as “ Theologus autodidactus”. This article does not focus on the content of this book but on the philological persepctive of how this book is edited by Joseph Schacht and Max Meyerhoff. Therefore, the question is whether this book which is edited by these two scholars is based on academic standards or not. Another question is how the editors study this text , particularly their main basis of editing this text.